Rummets betydelse för den museala utställningen - Pettersson, Richard (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
The museum exhibition relation to the visitor has been a major topic in museology research for a long time now. But in the recent, focus has been laid on the specific room whereupon the exhibition itself is located. This has raised some intricate questions: is the room itself interacting with the message making in the exhibition? And how are the visitors — which are dealing with the total interpretation of the room and the exhibition — dealing with this "message"? Are the visitors passive receptors or are they interacting with the meaning making in the exhibition room? These are complex questions which are creatively and thoughtfully analyzed from different angles in the following three separate articles from Eva Sofia Johansson, Louise Ahmt and Märit Simonsson.